2007
DOI: 10.1021/ol701653x
|View full text |Cite
|
Sign up to set email alerts
|

Acid- and Pd(0)-Catalyzed Ring Opening of 1-(1-Cycloalkenyl)cyclopropyl Sulfonates

Abstract: We report herein facile acid-catalyzed isomerization of 1-(1'-cycloalkenyl)cyclopropyl sulfonates under mild conditions. The remarkable ease of ring opening is attributed to the presence of a 1'-alkyl substituent. Also included is a palladium-catalyzed ring opening reaction of 1-(1'-cycloalkenyl)cyclopropyl tosylates for convenient preparation of substituted 1,3-dienylamines, which complements previously reported nucleophilic substitution reactions of (1-vinyl)cyclopropyl tosylates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Thus, for simplicity, Figure explores the trend in reactivity according to conditions that best represent a leaving group’s reactivity (see SI for full details). Cyclopropyl tosylate 1a , which is known to undergo S N 2′-type and S N 1 reactions,, selectively yielded the ring-opened product using NiCl 2 (PPh 3 ) 2 at 110 °C . Under the same conditions, mesylate 1b also selectively gave the ring-opened isomer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for simplicity, Figure explores the trend in reactivity according to conditions that best represent a leaving group’s reactivity (see SI for full details). Cyclopropyl tosylate 1a , which is known to undergo S N 2′-type and S N 1 reactions,, selectively yielded the ring-opened product using NiCl 2 (PPh 3 ) 2 at 110 °C . Under the same conditions, mesylate 1b also selectively gave the ring-opened isomer.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, cyclopropyl electrophiles reveal two-electron versus one-electron reactivity via the product obtained in a substitution reaction (Figure ). When cyclopropyl electrophiles are treated to two-electron substitution chemistry, the ring-opened product is typically obtained; concerted substitutions result in an S N 2′ pathway (Figure a, top arrow), while S N 1 reactions occur via rapid ring-opening of the cyclopropyl cation (Figure a, bottom arrow). , Alternatively, cyclopropyl radicals have a lifetime which allows them to be captured without rupture of the cyclopropane . Thus, the one-electron substitution process can retain the cyclopropane ring.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, cyclopropyl electrophiles reveal two-electron versus one-electron reactivity via the product obtained in a substitution reaction (Figure 1). When cyclopropyl electrophiles are treated to two-electron substitution chemistry, the ringopened product is typically obtained; concerted substitutions result in an SN2' pathway (Figure 1a, top arrow), 8 while SN1 reactions occur via rapid ring-opening of the cyclopropyl cation 9 (Figure 1a, bottom arrow). 10,11 Alternatively, cyclopropyl radicals have a lifetime which allows them to be captured without rupture of the cyclopropane.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recently, Cha and coworkers found that 1-alkenylcyclopropyl tosylates are amenable to ring-opening functionalization with nucleophiles such as amines in the presence of catalytic Pd. 9 However, the scope of this transformation is limited to 1-alkenyl-substituted cyclopropyl tosylates.…”
mentioning
confidence: 99%
“…Since some 1-substituted cyclopropyl tosylates can be ringopened and functionalized using catalytic Pd, 9 we began our investigation by exploring Pd catalysis to facilitate this reaction (Table 1). Using 1-phenylcyclopropyl tosylate (1a), 4-methoxyphenylboronic acid (2 equiv.…”
mentioning
confidence: 99%